2017
DOI: 10.1177/0962280217718867
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis without study-specific variance information: Heterogeneity case

Abstract: The random effects model in meta-analysis is a standard statistical tool often used to analyze the effect sizes of the quantity of interest if there is heterogeneity between studies. In the special case considered here, meta-analytic data contain only the sample means in two treatment arms and the sample sizes, but no sample standard deviation. The statistical comparison between two arms for this case is not possible within the existing meta-analytic inference framework. Therefore, the main objective of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…A random-effects model using the restricted maximum likelihood method was applied, as this model has been known to allow greater generalization of conclusions for variable patient populations and different surgical procedures. 29,52 Forest plots were used to show the outcomes, pooled estimate of effect, and overall summary effect of each study and were constructed using OpenMeta[Analyst] (Brown University; http://www.cebm.brown.edu/openmeta). Additional analyses were performed using Comprehensive Meta-Analysis software (Biostat) and R statistical software Version 3.4.0 (R Foundation for Statistical Computing).…”
Section: Methodsmentioning
confidence: 99%
“…A random-effects model using the restricted maximum likelihood method was applied, as this model has been known to allow greater generalization of conclusions for variable patient populations and different surgical procedures. 29,52 Forest plots were used to show the outcomes, pooled estimate of effect, and overall summary effect of each study and were constructed using OpenMeta[Analyst] (Brown University; http://www.cebm.brown.edu/openmeta). Additional analyses were performed using Comprehensive Meta-Analysis software (Biostat) and R statistical software Version 3.4.0 (R Foundation for Statistical Computing).…”
Section: Methodsmentioning
confidence: 99%
“…However, ~90% of included studies had no associated measure of within-study variance because the studies did not all use DEV as a response variable for individual samples. To address this limitation, we used a maximum likelihood estimation (MLE) and a random effects model to estimate heterogeneity for each study's observed mean difference, enabling us to fill in missing variance values (Sangnawakij et al, 2017).…”
Section: Predation Consumption Metricsmentioning
confidence: 99%
“…In the fixed-effects model, it was assumed that the various studies contributing to the problem of interest share the same true effect size, so that the estimated parameter is a common effect size for all studies (Sangnawakij et al 2019). In this context, the effect caused by the data derived from different studies was taken into account as homogeneous in the fixed-effects model.…”
Section: Fixed Regression Model: Fixed Effect + Effect Between Studiesmentioning
confidence: 99%
“…In contrast to the fixed regression model, the random-effects model treats the true effect size of the studies involved in the meta-analysis as a random sample of the population effect size distribution so that each group can contribute with a different effect (Sangnawakij et al 2019). In this context, the mixed regression model, similar to the fixed-effects model, takes into account the effect factor between groups (studies).…”
Section: Mixed Regression Model: Fixed Effect + Random Effect + Effect Between Studiesmentioning
confidence: 99%